A comparative assessment of the physical and microstructural properties of waste garnet generated from automated and manual blasting process. (June 2021) - Usman, Kabiru Rogo; Hainin, Mohd Rosli; Satar, Mohd Khairul Idham Mohd; Warid, Muhammad Naqiuddin Mohd; Usman, Aliyu; Al-Saffar, Zaid Hazim; Bilema, Munder Abdullah
Highlights: The level of contamination of spent garnet with toxic heavy metals was evaluated. Comparison of extent of heavy metals in auto and manually-generated spent garnets revealed both to be within safe limits. The auto-generated spent proves most desirable for incorporation as fine aggregate replacement in asphalt surface treatments. The high angularity of spent garnet can produce better performing asphalt mixtures with reduced rutting and fatigue cracking. Abstract: Cold mix asphalt (CMA) is an eco-friendly sustainable asphalt mixture, mostly for asphalt surface treatments (ASTs). However, material compatibility and poor adhesion leading to high voids, moisture damage susceptibility, and weak early strength remain challenging. Efforts to solve this limitation is beamed towards binder improvement and modification with modifiers, adhesion promoters, or polymers. Other forms of AST mixture improvement entail supplementary cementitious reinforcing or pozzolanic agents in the form of by-products. In this study, the physio-mechanical and microstructural desirability of spent garnet for use as fine aggregate in CMA was explored. Spent garnet is a by-product of abrasive blasting, often produced in large quantities and disposed of in landfills. Often, spent garnet waste gets contaminated with toxic elements either during usage or in landfills. This study aimed to investigate the properties of Automatically (AG) and Manually generated (MG) spent garnet grades. The physio-mechanical, morphologic, and chemical parameters of spent garnet were assessed to achieve this aim. The result compared with relevant specifications on cold mixtures plus Jabatan Kerja Raya (JKR) requirement. Moreover, crystallinity and composition were studied using Fourier transform infrared (FTIR) spectroscopy, X-ray diffraction (XRD), and X-ray Fluorescence (XRF). The presence of toxic heavy metals that often contaminate spent garnet deposits in landfills was evaluated too. Results suggested that both AG and MG's high sand equivalent and least water absorption of 98 %, 89 %, and 0.14 %, 0.23 % accordingly, and can replace sand in CMA. However, MG spent garnet is not desirable for chemically sensitive materials. The AG garnet was found to be Pyrope while the MG spent garnet is largely Almandine garnet – the strongest form of garnet, including traces of other garnet forms.